Synthesis of novel mast cell-stabilising and anti-allergic 1,2,3,4-tetrahydro-1-naphthalenols and related compounds - WALSH, JOHN JARLATH (Elsevier, 2011)
In a continuation of our studies into indan and tetralin systems as novel modulators of allergic and inflammatory phenomena, we have extended our work to include dimers linked via C-C bonds. Of these compounds, 2-Benzyl-2-[2-phenyl-1-ethenyl]-1,2,3,4-tetrahydro-1-naphthalenol 12 exhibited most promising activity both in vitro and in vivo.
PUBLISHED
Keywords: Biochemistry and molecular biology; mast cell